(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Capital structure plays a significant role in determining the financial health, risk profile, and valuation of firms. In the Indian corporate environment, capital structure decisions have gained increasing importance due to economic liberalization, rapid industrial growth, changing regulatory frameworks, and rising participation from domestic and international investors. Capital structure refers to the proportion of debt and equity used by firms to finance their operations and growth activities. The choice between debt and equity financing influences the cost of capital, financial risk, profitability, and shareholder value. Firms with higher debt levels may benefit from tax advantages but are exposed to greater financial risk and bankruptcy possibilities, whereas firms relying more on equity financing may maintain greater financial stability but face higher capital costs and ownership dilution. This study examines the relationship between capital structure and firm valuation among Indian firms by considering various internal and external determinants such as industry characteristics, firm size, ownership structure, market conditions, interest rates, and corporate governance practices. The study aims to identify patterns and insights regarding optimal financing decisions and their impact on firm valuation in the Indian business environment. The findings are expected to provide valuable implications for corporate managers, investors, and policymakers in making effective financial decisions and improving corporate performance.